On Identifying Phishing Emails and Websites using Content Analysis, URL Analysis, and Sender Behavior - Norman, Azah Anir (Journal of Information Systems Research and Practice, 2024)
With phishing attacks becoming increasingly sophisticated, traditional detection methods are struggling to keep pace, leading to significant cybersecurity vulnerabilities. This paper addresses the urgent need for more adaptable and accurate phishing detection mechanisms. It highlights the limitations of current systems, particularly their inability to effectively parse and understand the nuanced language of phishing emails. By contextualizing the problem within the broader landscape of escalating cyber threats, the paper sets the stage for the introduction of an innovative solution combining Natural Language Processing (NLP) and advanced machine learning techniques.